Optimizing Supply Chain Management To Increase Efficiency And Profitability In The Manufacturing Industry - Khaeriyah Khaeriyah; Fadli Mappisabbi; Muhammad Iqbal (Pusat Riset dan Inovasi Nasional, 2023)
The purpose of this study is to explore how optimizing supply chain management can improve efficiency and profitability in the manufacturing industry. Using case studies of specific manufacturing companies, this study identifies the various factors that influence supply chain performance and how optimizing these processes can improve a company's overall performance. The research method used is qualitative and quantitative analysis through in-depth interviews, observations, and secondary data analysis. The results of the study show that vertical integration, the use of information technology, and increased communication between parts of the supply chain are key factors in optimizing supply chain management. This research provides valuable information for manufacturing companies seeking to improve their efficiency and profitability through better supply chain management.”